Teologi PAK dan Gereja: Strategi Kontribusi dalam Pendidikan Teologi Agama Kristen - Karta, Endang Satria; Runesi, Serly Monita; Triwungsu, Ailin; Tapilaha, Sandra Rosiana (Pusat Riset dan Inovasi Nasional, 2025)
This article explores the relationship between the theology of Christian Religious Education (CRE) and the Church in contributing to relevant, contextual, and transformative theological education. The Church, as a community of faith and spiritual institution, plays a strategic role in shaping theological understanding through teaching, discipleship, and ministry. Meanwhile, CRE within the formal education system is tasked with delivering Christian values through pedagogical and academic approaches. In an era shaped by secularism, pluralism, and technological advancement, both challenges and opportunities arise for CRE and the Church to collaborate meaningfully. Through literature review and theological analysis, this article identifies key challenges such as the gap between theory and practice, limited human resources, and the influence of popular culture that often contradicts Christian values. On the other hand, significant opportunities exist, including the use of digital technology, the strengthening of faith-based character education, and the implementation of contextual approaches to theological teaching. The article affirms the importance of a strategic partnership between the Church and CRE in developing theological education that not only informs the mind but also transforms lives through strong Christian character in everyday contexts.